Beneficent Beauty: Refining the UW-Madison Campus - Brown, Gary; Okoli, Dan; Fish, Alan (My University, 2008)
Endowed with three and a half miles of lakeshore and more than 300 acres of natural areas preserve, the University of Wisconsin-Madison is a truly spectacular setting for a college campus. Furthermore, the location and design of campus can serve as a major asset to the aesthetic and spirit of the broader Madison community. But over time, the orchestration of certain physical attributes has either enhanced or detracted from its beauty. The new campus design review process provides a useful framework for creating buildings and settings that are as sublime as they are sustainable and functional and also help foster the ideal of the university as a good neighbor. A panel of individuals highly involved in the review will explore current strategies for implementing the new campus master plan and seek suggestions from the public and campus community through an intellectual and social exchange with the ultimate goal of enhancing everyone's experience of this extraordinary place.
Keywords: Outreach, Engagement, and the Public Good; Leadership and Governance